Can MR Imaging Diagnose Adult-Onset Alexander Disease? - Farina, L.; Pareyson, D.; Minati, L.; Ceccherini, I.; Chiapparini, L.; Romano, S.; Gambaro, P.; Fancellu, R.; Savoiardo, M. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: In recent years, the discovery that mutations in the glial fibrillary acidic protein gene (GFAP) were responsible for Alexander disease (AD) brought recognition of adult cases. The purpose of this study was to demonstrate that MR imaging allows identification of cases of AD with adult onset (AOAD), which are remarkably different from infantile cases.MATERIALS AND METHODS: In this retrospective study, brain and spinal cord MR imaging studies of 11 patients with AOAD (7 men, 4 women; age range, 26–64 years; mean age, 43.6 years), all but 1 genetically confirmed, were reviewed. Diffusion and spectroscopic investigations were available in 6 patients each.RESULTS: Atrophy and changes in signal intensity in the medulla oblongata and upper cervical spinal cord were present in 11 of 11 cases and were the diagnostic features of AOAD. Minimal to moderate supratentorial periventricular abnormalities were seen in 8 patients but were absent in the 3 oldest patients. In these patients, postcontrast enhancement was also absent. Mean diffusivity was not altered except in abnormal white matter (WM). Increase in myo-inositol (mIns) was also restricted to abnormal periventricular WM.CONCLUSIONS: Awareness of the MR pattern described allows an effective selection of the patients who need genetic investigations for the GFAP gene. This MR pattern even led to identification of asymptomatic cases and should be regarded as highly characteristic of AOAD.